Hierarchical clustering analysis of hydrogen bond networks in aqueous solutions. Issue 16 (12th April 2022) - Feng, Yixuan; Fang, Hongwei; Gao, Yitian; Ni, Ke
Abstract : To understand the relation between the macroscopic properties and microscopic structure of hydrogen bond networks in solutions, we introduced a hierarchical clustering method to analyze the typical configurations of water clusters in this type of network. Abstract : To understand the relation between the macroscopic properties and microscopic structure of hydrogen bond networks in solutions, we introduced a hierarchical clustering method to analyze the typical configurations of water clusters in this type of network. Regarding hydrogen bonds as frames, the rings, fragments and clusters are defined and analyzed to provide a comprehensive perspective for the distributional and dynamic characteristics of the hydrogen-bonding network in NaCl solution at different concentrations. The properties of the radial distribution function and hydrogen bonds are first analyzed. Destruction and shorter lifetimes of hydrogen bonds are observed in solutions. In further analysis of the two-dimensional configuration, i.e., ring, and three-dimensional configuration, i.e., fragment, the average number, size and lifetime of these structures consistently decrease as the concentration increases. Ionic effects on disrupting rings and fragments are significant in the first hydration shell, especially with sodium cations, and these effects weaken beyond the first hydration shell. Regarding the clusters obtained using the Louvain algorithm, our results indicate that clusters break and become smaller as the NaCl concentration increases. The presence of ions also leads to the isolation of clusters and therefore the inhibition of changes. The lifetime of clusters increases with NaCl concentration, indicating the slowed breakage and reformation of clusters in NaCl solutions. This method can be further applied to quantitatively characterize hydrogen bond networks to elucidate more properties of aqueous solutions.